ANALISIS FAKTOR YANG MEMPENGARUHI STRES KERJA PERAWAT DI RAWAT INAP RS PELAMONIA MAKASSAR - Mohammad Ardani Samad; Andi Nadya (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2022)
Work stress is an excessive workload, feelings of difficulty and emotional tension that hinder individual life so that it can cause stress. the number of patients in the hospital that is not proportional to the number of nurses on duty in the inpatient room makes nurses experience stress, fatigue. The purpose of this study was to determine the factors that affect the work stress of nurses in the inpatient ward of the Pelamonia Hospital, Makassar. Quantitative research design with a cross sectional approach. The sample of this study was 183 nurses in the inpatient room of the Pelamonia Hospital Makassar. Sampling technique using accidental. the data was processed using the Chi Square test. The results of this study are intrinsic factor values obtained (p = 0.011), individual roles in work organizations (p = 0.126), work relations obtained (p = 0.397 ), individual personalities (p = 0.010), individual roles in work organizations (p = 0.852), family factor (p=0.041). So it can be concluded that from several factors there are three factors that influence significantly, namely intrinsic factors, individual personality, and family factors.It is recommended to the hospital to readjust the number of nurses working in each room so that there is a balance between the number of nurses and the number of patients in the inpatient room so that it does not can trigger stress on nurses.